Anaemia and related nutrient deficiencies after Roux-en-Y gastric bypass surgery: a systematic review and meta-analysis. Issue 7 (16th July 2015) - Weng, Ting-Chia; Chang, Chia-Hsuin; Dong, Yaa-Hui; Chang, Yi-Cheng; Chuang, Lee-Ming
Abstract : Objective: To obtain a pooled risk estimate on the long-term impact of anaemia and related nutritional deficiencies in patients receiving Roux-en-Y gastric bypass (RYGB) surgery. Design: Systematic review and meta-analysis. Data sources: MEDLINE, EMBASE and Cochrane databases were searched to identify English reports published before 16 May 2014. Eligibility criteria: Articles with case numbers >100, follow-up period >12 months, and complete data from both before and after surgery were selected. Outcomes of interest were changes in baseline measurements of proportion of patients with anaemia, by haemoglobin, haematocrit, ferritin, iron, vitamin B12 and folate levels. Data collection and analysis: Two reviewers independently reviewed data and selected six prospective and nine retrospective studies with a total of 5909 patients. A random effect model with inverse variance weighting was used to calculate summary estimates of outcomes at 6, 12, 24 and 36 months postoperatively. Results: Proportion of patients with anaemia was 12.2% at baseline, which, respectively, increased to 20.9% and 25.9% at 12 and 24 months follow-up, consistent with decreases in haemoglobin and haematocrit levels. Although the serum iron level did not change substantially after surgery, the frequency of patients with ferritin deficiency increased from 7.9% at baseline to 13.4% and 23.0% at 12 and 24 months, respectively, postoperation. Vitamin B12 deficiency increased from 2.3% at baseline to 6.5% at 12 months after surgery in those subjects receiving RYGB. There was no obvious increase in folate deficiency. Conclusions: RYGB surgery is associated with an increased risk of anaemia and deficiencies of iron and vitamin B12, but not folate. Ferritin is more sensitive when serum iron level is within normal range.